Dual-Targeted Therapy Circumvents Non-Genetic Drug Resistance to Targeted Therapy - Wang, Wei; Sun, Yue; Liu, Xiaobo; Kumar, Shaji K.; Jin, Fengyan; Dai, Yun (Frontiers in Oncology, 2022)
The introduction of various targeted agents into the armamentarium of cancer treatment has revolutionized the standard care of patients with cancer. However, like conventional chemotherapy, drug resistance, either preexisting (primary or intrinsic resistance) or developed following treatment (secondary or acquired resistance), remains the Achilles heel of all targeted agents with no exception, via either genetic or non-genetic mechanisms. In the latter, emerging evidence supports the notion that intracellular signaling pathways for tumor cell survival act as a mutually interdependent network via extensive cross-talks and feedback loops. Thus, dysregulations of multiple signaling pathways usually join forces to drive oncogenesis, tumor progression, invasion, metastasis, and drug resistance, thereby providing a basis for so-called "bypass" mechanisms underlying non-genetic resistance in response to targeted agents. In this context, simultaneous interruption of two or more related targets or pathways (an approach called dual-targeted therapy, DTT), via either linear or parallel inhibition, is required to deal with such a form of drug resistance to targeted agents that specifically inhibit a single oncoprotein or oncogenic pathway. Together, while most types of tumor cells are often addicted to two or more targets or pathways or can switch their dependency between them, DTT targeting either intrinsically activated or drug-induced compensatory targets/pathways would efficiently overcome drug resistance caused by non-genetic events, with a great opportunity that those resistant cells might be particularly more vulnerable. In this review article, we discuss, with our experience, diverse mechanisms for non-genetic resistance to targeted agents and the rationales to circumvent them in the treatment of cancer, emphasizing hematological malignancies.